Excitatory amino acid antagonists and pentylenetetrazol-induced seizures during ontogenesis: III. The action of kynurenic acid and glutamic acid diethylester - Velísek, L; Roztocilová, L; Kusá, R; Mares, P (Brain research bulletin, 1995)
N-methyl-D-aspartate (NMDA) receptor antagonists are anticonvulsant drugs with specific activity against tonic-clonic pentylenetetrazol-induced seizures. However, they do not affect clonic seizures with preserved righting reflexes. In these experiments, we tested the anticonvulsant activity of strychnine-insensitive glycine receptor (at the NMDA site) antagonist kynurenic acid and nonspecific excitatory amino acid receptor antagonist glutamic acid diethylester (GDEE) in the pentylenetetrazol-induced seizure model in developing rats 7, 12, 18, 25, and 90 days old. Control rats were injected with pentylenetetrazol (100 mg/kg subcutaneously). Other rats were pretreated either with kynurenic acid (40, 80, or 240 mg/kg IP) or with GDEE (0.48-480 mg/kg IP), followed by pentylenetetrazol (100 mg/kg). In very young rats (7 and 12 days), both kynurenic acid and GDEE increased the incidence of clonic seizures, whereas the occurrence of tonic-clonic seizures was suppressed or delayed compared to controls. This effect is very similar to the anticonvulsant action of the competitive and noncompetitive NMDA receptor antagonists. In adult rats, the pretreatment with rather higher doses of kynurenic acid or GDEE suppressed or delayed clonic seizures as well as tonic-clonic seizures. Both drugs also induced behavioral side effects: repetitive orientation, wet dog shakes, and frequent jumping. Our data show that there are only weak and nonconsistent age-specific anticonvulsant effects resulting from the blockade of strychnine-insensitive glycine receptor often associated with serious side effects, thus decreasing chances to develop effective antiepileptic treatment in this drug class.
Keywords: Pentylenetetrazole; Animals; Rats, Wistar; Seizures; Age Factors; Kynurenic Acid; věkové faktory; pentylentetrazol; kyselina glutamová; Receptors, N-Methyl-D-Aspartate; Male; modely nemocí na zvířatech; kyselina kynurenová; Disease Models, Animal; krysa rodu Rattus; receptory N-methyl-D-aspartátu; zvířata; mužské pohlaví; Rats; Glutamic Acid; záchvaty; potkani Wistar